Raising Awareness of Therapeutic Misconception and Optimism Around Clinical Trials in Huntington’s Disease - de Bot, Susanne Tamara (J Huntingtons Dis, 2019)
The Huntington’s disease (HD) community is moving into an exciting time with Huntingtin lowering strategies entering human clinical trials. These upcoming targeted therapeutic approaches for this devastating disease with unmet medical needs, are believed to be a last resort for many patients and their families. Recently, patients with HD were shown to be at high risk for therapeutic misconception, mistaking research for actual treatment. It is important that investigators are aware of their patient’s, as well as their own, vulnerability to therapeutic misconception. To limit therapeutic misconception, information should be provided on the rationale for clinical trials and the differences between clinical research and clinical care should be carefully discussed.